(untitled) (Bangladesh Journal of Agricultural Research, 2018)
In Bangladesh groundnut shelling is done manually which is laborious, time consuming and costly. Shelling of groundnut pod with the help of mechanical power can be a probable solution of this problem. A power groundnut sheller was designed and fabricated in Farm Machinery and Postharvest Process Engineering (FMPE) Division, Bangladesh Agricultural Research Institute (BARI), Gazipur during 2011-13. The sheller was made of Mild Steel (MS) angle bar, MS flat bar, MS rod, MS sheet, MS sieve, rubber pad etc. The shelling capacities of power groundnut sheller were 110 and 115 kg/h for Dhaka-1 and BARI Badam-8, respectively. Average breakage of groundnut kernel was 2% at 7.5% moisture content (wb). The maximum and minimum unshelled pods were about12.4% and 9.18% for Dhaka -1 and BARI Badam-8, respectively. The shelling efficiency of the power groundnut sheller for Dhaka-1 and BARI Badam-8 were 86.6 and 88.82% respectively at 11.5% moisture content (wb). Winnowing efficiency was found to be 99% in the power groundnut sheller. The use of power groundnut sheller can reduce the cost of shelling by 76% over the manual groundnut sheller. This power groundnut sheller is recommended for shelling of groundnut at farm level and small industry level in Bangladesh. Bangladesh J. Agril. Res. 43(4): 631-645, December 2018